Rsp promotes the transcription of virulence factors in an agr-independent manner in Staphylococcus aureus - Banghui Liu; Baolin Sun (Emerging Microbes and Infections)
Staphylococcus aureus is a major human pathogen that causes a great diversity of community- and hospital-acquired infections. Rsp, a member of AraC/XylS family of transcriptional regulators (AFTRs), has been reported to play an important role in the regulation of virulence determinants in S. aureus via an agr-dependent pathway. Here we demonstrated that Rsp could bind to the rsp promoter to positively regulate its own expression. We then constructed an isogenic rsp deletion strain and compared the haemolysis in the wild-type and rsp mutant strains. Our results indicated that the rsp mutant strain displayed decreased haemolytic activity, which was correlated with a dramatic decrease in the expression of hla and psm. Furthermore, we analysed the regulatory effects of Rsp in the agr mutant strain and found that they are agr-independent. Electrophoretic mobility shift assay indicated that Rsp can directly bind to the promoter regions of hla and psm. The mouse model of subcutaneous abscess showed that the rsp mutant strain displayed a significant defect in virulence compared to the wild-type strain. These findings reveal that Rsp positively regulates the virulence of S. aureus by promoting the expression of hla and psm through direct binding to their promoter regions.